Excitable speech: A politics of the performance - Butler, Judith (Routledge, 1997)
‘When we claim to have been injured by language, what kind of claim do we make?’ - Judith Butler, Excitable Speech Excitable Speech is widely hailed as a tour de force and one of Judith Butler’s most important books. Examining in turn debates about hate speech, pornography and gayness within the US military, Butler argues that words can wound and linguistic violence is its own kind of violence. Yet she also argues that speech is ‘excitable’ and fluid, because its effects often are beyond the control of the speaker, shaped by fantasy, context and power structures. In a novel and courageous move, she urges caution concerning the use of legislation to restrict and censor speech, especially in cases where injurious language is taken up by aesthetic practices to diminish and oppose the injury, such as in rap and popular music. Although speech can insult and demean, it is also a form of recognition and may be used to talk back; injurious speech can reinforce power structures, but it can also repeat power in ways that separate language from its injurious power. Skillfully showing how language’s oppositional power resides in its insubordinate and dynamic nature and its capacity to appropriate and defuse words that usually wound, Butler also seeks to account for why some clearly hateful speech is taken to be iconic of free speech, while other forms are more easily submitted to censorship. In light of current debates between advocates of freedom of speech and ‘no platform’ and cancel culture, the message of Excitable Speech remains more relevant now than ever.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; fem1000; performativité; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; états-unis

Feminist contentions: A philosophical exchange - Benhabib, Seyla; Butler, Judith; Cornell, Drucilla; Fraser, Nancy (Routledge, 1995)
Ce volume présente un débat entre quatre des plus grandes théoriciennes féministes des États-Unis. Seyla Benhabib, Judith Butler, Drucilla Cornell et Nancy Fraser discutent de certaines des questions clés auxquelles la théorie féministe est confrontée. Chacune articule sa propre position dans un essai initial, puis répond aux autres dans un essai de suivi, rendant possible une conversation entre ces penseuses féministes influentes. Commencé comme un symposium sur la question du féminisme et du postmodernisme, le volume s'est transformé en une discussion sur des questions plus larges telles que l'utilité du postmodernisme en tant que concept théorique; le rôle de la philosophie dans la critique sociale ; comment le récit historique est le mieux conceptualisé ; le statut du sujet du féminisme ; et les effets politiques des différentes formulations de toutes ces questions.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; genre; identités LGBTQIA2+; philosophie; postmodernisme; périodes historiques; régions géographiques; sciences humaines; thématiques; états-unis